The Impact of Climatic and Environmental Factors on the Frequency of Natural Disasters in the Insurance Sector in G7 Countries - Serap Yörübulut (Doğal Afetler ve Çevre Dergisi)
In this study, the effects of temperature, precipitation, greenhouse gas emissions and load capacity factor (LCF), which is one of the environmental sustainability indices, on the frequency of natural disasters occurring in G7 countries between 1989-2022 were evaluated by panel data analysis method. The findings obtained show that increasing greenhouse gas emissions, precipitation and temperature due to climate change increase the number of natural disasters, while the decrease in the LCF factor increases the number of natural disasters. While Pedroni and Kao cointegration tests reveal the existence of a long-term relationship between the variables, the Panel Error Correction Model (ECM) results corrected with Driscoll-Kraay standard errors show that greenhouse gas emissions and the LCF factor, which seem to be ineffective in the short term, become determinants of the frequency of natural disasters in the long term. The increasing frequency and severity of natural disasters due to the impact of climate change and environmental factors reveal that insurance systems are an important risk management tool against such events. In the context of G7 countries, it is suggested that regulatory frameworks should be strengthened, public-private partnerships should be increased and advanced risk modeling techniques should be adopted to ensure the adaptation of the insurance sector to climate change. This study contributes to the literature by using LCF as an innovative factor in examining disaster dynamics and by presenting suggestions for the development of long-term risk management policies for the insurance sector.